Educational assessment: a reality in the museum - Gutiérrez Berciano, Sué; Calaf, Roser (Pulso. Revista de educación, 2013)
This work has been the pilot test of the Qualitative Evaluation of Educational Programs in Spain pro¬ject, (ECPEME) developed in 2011. The choice of both museums, Casa Natal de Jovellanos and Piñole Nicanor de Gijón (Asturias), as the first stage of evaluation, is justified by the presence of a well-established educational program with more than 20 years of tradition and the close school-museum relationship (85% of the municipalitys schools participate in activities), as well as the continuity of the person in charge of designing and implementing the promoted educational ac¬tivities. We have followed the logic procedures of the Illuminative Evaluation Parlett and Hamilton (Stufflebeam and Shinkfield, 1995) in order to develop a proposal for evaluation of educational interventions conducted at the museum. Using a combination of methodological protocols, allowing us to achieve a deeper and more rigorous analy¬sis of the educational effectiveness of museum educators. Aiming to understand not only aspects of their teaching performance but also of their working conditions.